Cotton, capital, and colonialism in southern Korea, 1910-1945: Semi-governmental organizations in the construction of imperial agriculture - Stephens, Holly (Modern Asian Studies, 2024)
This article investigates cotton promotion policies in colonial Korea, with a focus on the role of a series of semi-governmental organizations (SGOs) in implementing colonial policies to shape farmers' interactions with global, capitalist markets. Colonia
Keywords: Agriculture; Colonial State; Cotton; Korea; Capitalism